CRIMINAL RESPONSIBILITY AGAINST VILLAGE HEADS WHO COMMIT CRIMINAL ACTS OF VILLAGE FUND CORRUPTION - Utreck Ricardo; Yasmirah Mandasari Saragih; Rahmayanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Corruption is a special criminal act. One form of equitable and just national development is development carried out not only in urban areas, but also in rural areas through the provision of Village Funds from state finances. However, the state's efforts, in this case the central government, to develop villages seem to be hampered by criminal acts of corruption committed by unscrupulous Village Heads. The problem formulation that will be the main topic of discussion is what are the legal procedures for managing Village Funds which originate from State Finance? What is the criminal responsibility for individual Village Heads who commit criminal acts of Village Fund corruption? This research is normative juridical research, namely research that refers to legal norms contained in Legislation, Court Decisions and legal norms that exist in society regarding what happens in reality in society which is related to the research material. In this research, it can be concluded that individual Village Heads who commit criminal acts of Village Fund corruption can be charged under Article 2 or Article 3 in conjunction with Article 18 Paragraph (1) letter b of Law of the Republic of Indonesia Number 20 of 2001 concerning Amendments to the Law of the Republic of Indonesia Number 31 of 1999 concerning Eradication of Corruption Crimes. The author's advice to law enforcement officials, especially the justice profession, is to prioritize the principles of law enforcement in deciding cases and in giving punishment to corruptors in Indonesia.